Peran Kyai Dalam Membentuk Adversity Quotient Santri: The Role of Kyai in Shaping the Adversity Quotient of Santri - Surur, Miftahus; Abdurrahman, Moh. Fiki; Rasyyidi, Ahmad Hafas (Halaqa: Islamic Education Journal, 2019)
Kyai has an important role in the birth and growth of a pesantren, including Salafiyah Dawuhan Pesantren in Situbondo. The style and development of pesantren are very much influenced by the expertise, knowledge and ability of a Kyai, including in educating students. This study aims to determine the role of clerics in forming adversity quotient santri in Salafiyah Dawuhan Pesantren Dawuhan Situbondo through a qualitative description approach with two variables, one X variable and one Y variable. Data collection techniques use the triangulation method, while in determining the sample using the purposive method and snowball sampling. This research successfully illustrates that the Kyai has a very vital role in shaping the santri adversity quotient both individually and through collective work.